2022
DOI: 10.3389/fcvm.2022.857952
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cardiorenal Protection With SGLT2 Inhibitors in Patients With T2DM Based on Network Pharmacology

Abstract: PurposeSodium-glucose cotransporter 2 (SGLT2) inhibitors have cardiorenal protective effects regardless of whether they are combined with type 2 diabetes mellitus, but their specific pharmacological mechanisms remain undetermined.Materials and MethodsWe used databases to obtain information on the disease targets of “Chronic Kidney Disease,” “Heart Failure,” and “Type 2 Diabetes Mellitus” as well as the targets of SGLT2 inhibitors. After screening the common targets, we used Cytoscape 3.8.2 software to construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 155 publications
1
6
0
Order By: Relevance
“…This excessive glycolytic activity results in enhanced MGO concentration 46 . Inducing ERK1/2 MAPK with SGLT2 inhibitors has the potential to promote an increase in Glo1 activity and a decrease in MGO concentration, as it has been recognized as a crucial element within the cardioprotective pathway that mitigates damage during reperfusion 43 . However, empagliflozin pretreatment prevents severe fatal ventricular arrhythmia, likely through glucose‐independent ERK1/2 activation 47 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This excessive glycolytic activity results in enhanced MGO concentration 46 . Inducing ERK1/2 MAPK with SGLT2 inhibitors has the potential to promote an increase in Glo1 activity and a decrease in MGO concentration, as it has been recognized as a crucial element within the cardioprotective pathway that mitigates damage during reperfusion 43 . However, empagliflozin pretreatment prevents severe fatal ventricular arrhythmia, likely through glucose‐independent ERK1/2 activation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, this inhibition contributes to decreased formation and progression of atherosclerotic plaques. 43,44 In lipopolysaccharidestimulated human coronary artery endothelial cells, it is noteworthy that canagliflozin, as opposed to empagliflozin or dapagliflozin, effectively mitigates inflammation and reduces hexokinase II expression. This reduction is achieved through the inhibition of ERK1/2 phosphorylation.…”
Section: But Upregulatesmentioning
confidence: 99%
See 1 more Smart Citation
“…SGLT2is have an excellent diuretic and metabolic effect, as well as they may exert several other mechanisms, including neurohormonal modulation and reducing oxidative stress, inflammation and cardiovascular remodeling [ 172 ] ( Figure 2 ). Experimental and clinical studies have demonstrated an excellent nephroprotective effect for this class of drugs, even stronger than that shown by ACEi or ARBs, which are considered the most effective drugs for preserving kidney function in HF patients [ 173 , 174 ].…”
Section: Therapeutic Strategies In Crsmentioning
confidence: 99%
“…Accordingly, HFpEF can be classified into different phenotypes based on various criteria, including underlying etiology, clinical characteristics, and comorbidities [ 3 , 4 , 5 , 6 , 7 , 8 ]. Detailed molecular signaling, gene ontology functional analysis, and the use of the Kyoto Encyclopedia of Genes and Genomes pathway also potentiate the precise mechanisms of action and targets of SGLT2 inhibitors in clinical practice [ 9 , 10 ]. A comprehensive understanding and the specific pathways identified from HFpEF phenotyping also facilitate animal experimental studies to address relevant pathophysiological signaling [ 11 ].…”
Section: Introductionmentioning
confidence: 99%